Analysis of Factors Affecting Cranial Nerve Function of Patients With Vascular Mild Cognitive Impairment Through Functional Magnetic Resonance Imaging Under Artificial Intelligence Environment - Zhang, Lifang; Li, Yanran; Bian, Lin; Luo, Qingrong; Zhang, Xiaoxi; Zhao, Bing (Frontiers in Public Health, 2022)
The study aimed to explore the risk factors of effects of patients with vascular mild cognitive impairment (VaMCI) through functional magnetic resonance imaging (fMRI). In this study, 62 patients were selected from the department of neurology, admitted to Changzhi People's Hospital from October 1, 2018 to February 1, 2020. Patients with VaMCI were defined as the VaMCI group according to Clinical Dementia Rating (CDR), and subjects with normal cognitive function were defined as the normal control (NC) group. All patients underwent fMRI to identify the amplitude low-frequency fluctuation (ALFF) and regional homogeneity (ReHo) values, and to analyze their association with VaMCI. The results showed that the VaMCI group had lower scores for Mini-mental State Examination (MMSE), Montreal Cognitive Assessment (MoCA), and their subitems (visual space and execution, recall, attention and computation, and language ability) than NC group, with statistical differences (P < 0.05). In VaMCI group, the brain regions with increased ALFF values were the left temporal lobe, left parietal lobe, right temporal lobe, right parietal lobe, and posterior cingulate gyrus. Of them, the left parietal lobe and right temporal lobe were negatively correlated with the recall score on MMSE scale (r = −0.216, r = −0.132, P < 0.01). In VaMCI group, the brain regions with decreased ReHo values were the left temporal lobe, occipital lobe, and left middle temporal gyrus. Of them, the left temporal lobe and occipital lobe were positively correlated with MoCA score (r = 0.473, r = 0.848, P < 0.01). In conclusion, VaMCI patients have cognitive impairment and abnormally increased spontaneous brain activity, especially in the left parietal lobe and the right temporal lobe. At rest, VaMCI patients show decreased whole-brain ReHo in the left medial temporal lobe and occipital lobe. Hypertension is a high-risk factor for cognitive impairment in VaMCI patients. The study can provide a theoretical basis for early diagnosis of VaMCI.